PERSEPSI KEMUDAHAN PENGGUNAAN DAN KEPERCAYAAN TERHADAP MINAT NASABAH - Sri Ekowati; Reka Septi Amelia (UM. Bengkulu, 2021)
This study aims to determine the effect of perceived ease of use and trust in customer interest in using mobile banking (Case Study of BRI Unit Sukowati Customers, Rejang Lebong District), either partially or simultaneously. There are several factors that will be discussed in this study, including Perceived Ease Of Use and Trust. The object of this research is that customers use mobile banking (Case Study of BRI Unit Customers in Sukowati, Rejang Lebong Regency), totaling 50 people. In this research the authors use the method of data collection by means of observation, distributing questionnaires or questionnaires. Data analysis techniques used in this study, including by using instrument test, classical assumption test, respondent analysis analysis, multiple linear regression analysis, determinant coefficient, and hypothesis testing.The results showed that Perceived Ease Of Use had a positive effect on customer interest in using mobile banking at BRI Unit Sukowati customers, Kab. Rejang Lebong. This means that the convenience provided makes customers feel confident and confident about using mobile banking for every transaction. Then the trust variable has a positive effect on customer interest in using mobile banking at BRI Unit Sukowati customers, Kab. Rejang Lebong. This means that trust is very important in influencing customer interest in deciding whether or not to use the mobile banking application facility. So it can be concluded that Perceived Ease Of Use, and Trust partially and simultaneously affect the interest of customers using mobile banking (A Case Study of the BRI Unit Customer Sukowati, Rejang Lebong Regency)Keywords: Perceived Ease Of Use, Customer Trust and Interest.